Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation Dalam Meningkatkan Hasil Belajar Materi Sifat-Sifat Cahaya Siswa - St Maryam M; Rasmi Djabba; Suci Rahman (Universitas Negeri Makassar, 2022)
This research examines the Applying Of Cooperative Learning Model Type Of Group Investigation To Increase Students Achievement Topic The Nature Of Light Grade IV UPTD SD Negeri 58 Parepare. The problem of this research are 1) How can the applying of cooperative learning model type of group investigation can increase student process topic the nature of light grade IV UPTD SD Negeri 58 Parepare? 2) Can the applying of cooperative learning model type of group investigation to increase achievement students topic the nature of light grade IV UPTD SD Negeri 58 Parepare?. The type of research used is Classroom Action Research (CAR) and the approach used is a qualitative approach. The stages of classroom action research consist of 4 stages, namely planning, implementation, observation and reflection. The subjects in this research were fourth grade students of UPTD SD Negeri 58 Parepare for the academic year 2021/2022, totaling 16 students, as well as a teacher. Based on the data obtained during the implementation of the first cycle and second cycle, the results of the research for the first cycle of student learning outcomes with a completeness percentage of 73.43% were in the sufficient category (C). Meanwhile, for the second cycle, the percentage of completeness was 83.37% which was in the good category (B). From this research, it can be concluded that the process and student achievement Topic The Nature Of Light Grade IV UPTD SD Negeri 58 Parepare by applying the group investigation type cooperative learning model has increased.